International experience in anti-theft of catalytic converters installed in cars. - Pertsev, Roman (Archives of Criminology and Forensic Sciences, 2021)
Recently, there has been increase in the number of property crimes in the world, including theft of external car parts. The number of thefts of catalytic converters installed in cars of various brands has sharply increased due to a significant increase in the value of precious metals such as platinum, palladium and rhodium. The reason for a sharp increase in the number of crimes of this particular car part is small amounts of the mentioned precious metals in the catalytic convertors. The purpose of this article is to consider this problem faced by law enforcement and legislative bodies in many countries and to propose certain ways for its solution. The article provides an overview of the situation with thefts of catalytic converters in the countries of the European Union, the United States and Israel. Detailed reasons for the occurrence of this problem are provided, as well as measures to protect a car from the theft are suggested. Possible legislative and investigative-forensic actions to prevent this type of crime are considered: - law enforcement agencies investigating this type of crime should clearly understand that we are not talking about isolated, unrelated cases, but about well-planned actions of criminal groups. - increase in control over purchase and sale of metal carried out without accounting and corresponding documentation and amendments to the administrative procedural code also require strengthening. - applying a special forensic marking on parts, including on a catalytic converter, will allow to track its location and provide full information to law enforcement agencies from which vehicle it was stolen in the event of its theft. - inspection and examination by a forensic expert of vehicles and other physical evidence left by criminals at crime scenes for criminals’ fingerprints and DNA profiles will help to significantly increase the detection rate of this type of crime.